Integrated analysis of ATAC-seq and RNA-seq reveals ADSCP2 regulates oxidative phosphorylation pathway in hypertrophic scar fibroblasts - Qian Li; Zhe Quan; Ling Chen; Yiliang Yin; Xin Chen; Jingyun Li (PeerJ)
The primary effector cells involved in the formation of hypertrophic scars are fibroblasts. A potential peptide, ADSCP2 (adipose-derived stem cell peptide 2, the peptide fragment of ALCAM protein), derived from adipose-derived stem cell-conditioned medium, has been identified as having the potential to mitigate hypertrophic scar formation by targeting pyruvate carboxylase. However, the underlying mechanisms remain incompletely understood. Whether ADSCP2 attenuates hypertrophic scar fibrosis at the transcription level remains unclear. Consequently, this study sought to elucidate the potential mechanism associated with ADSCP2 by examining genome-wide transcriptional alterations and changes in chromatin accessibility in fibroblasts. This was achieved through the integrated analysis of assay for transposase accessible chromatin using sequencing (ATAC-seq) and RNA sequencing (RNA-seq). In the ADSCP2 treatment group, ATAC-seq identified a total of 7,805 differential peaks associated with 3,176 genes. RNA-seq analysis revealed 345 upregulated and 399 downregulated transcripts in the same group. A combined Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of both downregulated genes and close-ACRs (accessible chromatin regions) genes within the ADSCP2 treatment group indicated regulation of the oxidative phosphorylation pathway (OXPHOS) by ADSCP2. The amalgamation of ATAC-seq and RNA-seq data elucidates that two OXPHOS associated genes, namely COX6B1 (cytochrome c oxidase subunit 6B1) and NDUFA1 (NADH dehydrogenase (ubiquinone) alpha subcomplex-1), demonstrate significant downregulation in the presence of ADSCP2. Further analysis using the integrative genomics viewer indicates that the promoter regions of both COX6B1 and NDUFA1 exhibit a higher degree of closure in the ADSCP2 treatment group. Quantitative PCR analysis demonstrated that ADSCP2 treatment resulted in a reduction of COX6B1 and NDUFA1 mRNA expression levels. Furthermore, cellular ATP and lactic acid concentrations were diminished in the ADSCP2-treated group. Collectively, these findings suggest potential avenues for future research into the therapeutic application of the peptide ADSCP2 in the treatment of hypertrophic scars.